Four-terminal perovskite tandem solar cells - Muhammad Rafiq; Hengyue Li; Junliang Yang (iEnergy)
One of the primary barriers to the advancement of high-efficiency energy conversion technologies is the Shockley–Queisser limit, which imposes a fundamental efficiency constraint on single-junction solar cells. The advent of multi-junction solar cells provides a formidable alternative to this obstacle. Among these, organic-inorganic perovskite solar cells (PSCs) have captured substantial interest due to their outstanding optoelectronic properties, including tunable bandgaps and high-power conversion efficiencies, positioning them as prime candidates for multi-junction photovoltaic systems. We give a review of the latest advancements in four-terminal (4T) perovskite tandem solar cells (TSCs), emphasizing four pertinent configurations: perovskite-silicon (PVK/Si), perovskite-perovskite (PVK/PVK), perovskite-Cu(In,Ga)Se2 (PVK/CIGS), and perovskite-organic (PVK/organic), as well as other emerging 4T perovskite TSCs. Further, it also emphasizes the advancement of semitransparent wide-bandgap PSCs for TSC applications, tackling important issues and outlining potential future directions for optimizing 4T tandem design performance.